State history and economic development: Evidence from six millennia - Oana Borcan; Ola Olsson; Louis Putterman (Brown University, Department of Economics, 2014)
All since the rise of the first civilizations, economic development has been closely intertwined with the evolution of states. In this paper, we contribute to the literature on state history and long-run economic development in four ways. First, we extend and complete the state history index from Bockstette, Chanda and Putterman (2002) by coding the experience with states from the first state origins, 3500 BCE, up until 2000 CE. Second, we explore empirically the relationship between time since transition to agriculture and state age, as well as subsequent state history. Our estimated unconditional correlation implies that a 1000 year earlier transition to agriculture is associated with a 470 years earlier emergence of state institutions. We show how this relationship differs between indigenously- and externally- originated states. Third, we show that the relationship between our extended state history index and current levels of economic development has the shape of an inverted u. The results reflect the fact that countries that were home to the oldest states, such as Iraq, Egypt and China, are poorer today than younger inheritors of their civilizations, such as Germany, Denmark and Japan. This pattern was already in place by 1500 CE and is robust to adjusting for migrations during the colonial era. Finally, we demonstrate a very close relationship between state formation and the adoption of writing.
Keywords: O11; O43; O50; N00; 330; State history; comparative development